Vygotsky Theory Based on Mathematics Literacy in The New Normal Era - Nila Ubaidah; Dwijanto Dwijanto; Scolastika Mariani (Program Studi Tadris Matematika IAIN Salatiga, 2022)
Theory teaching and learning very calculated in influencing a history and culture as well as confess that school, besides reproduce knowledge, also reproduce injustice social. This article focuses on activity of literacy mathematics through interaction social in context certain, no on performance Skills someone 's math in isolation from context. It is in focus on practice activity literacy mathematics as culture, history, and political. Perspective practice social on literacy mathematics no ignore importance learning based school or skills technical. This paper aims to convey the actualization of theory based literacy math, so could give contribution.